EP510 Robotic surgery: does high body mass index (BMI) matter?. (1st November 2019) - Drymiotou, S; Dokmeci, AM; Chandrasekaran, D; Dilley, J; Rai, N; Lawrence, A; Manchanda, R; Phadnis, S; Jeyarajah, A; Brockbank, E
Abstract : Introduction/Background: Obesity increases endometrial cancer risk; 1.6-fold with every 5 kg/m 2 increase in BMI. High BMI is associated with additional surgical and anaesthetic risks and prolonged operating time. Robotic surgery is a promising route in obese women. Short-term data show no statistically significant difference in survival rates between robotic and abdominal (Hinshaw et al . 2016) and laparoscopic surgery for endometrial cancer (Corrado et al . 2018). The aims were to review whether the introduction of robotic surgery has increased minimally invasive surgery (MIS) rate in obese women and to assess the effect of BMI on console time. Methodology: Data was prospectively collected for all women undergoing surgery for endometrial cancer in a London tertiary unit in 2016 and 2018 (robotic surgery was introduced in 2017) and analysed using Microsoft Excel. Results: In 2016, 95 women had surgery. Following examination under anaesthetic, 53 (56%) had total abdominal hysterectomy (TAH) and 42 (44%) total laparoscopic hysterectomy (TLH). In 2018, 103 underwent surgery; 37 (35%) TAH and 66 (65%) MIS, of which 21 (31%) had TLH and 45 (69%) robotic hysterectomy (RAH). The mean BMI for MIS in 2018 was 36.2 kg/m 2 vs 32.2 kg/m 2 in 2016 (p=0.023). BMI range was 16–53 kg/m 2 in 2016 and 25–62 kg/m 2 in 2018. For BMI >30 kg/m 2, 21/42 (50%) had MIS in 2016 vs 42/66 (64%) in 2018 (p=0.02). In 2016, the median length of stay (LOS) was 5 days for BMI >30 undergoing MIS vs 1 day in 2018 (p=0.04). BMI had no impact on console time (p=0.064). Conclusion: The introduction of robotic surgery has significantly increased the MIS rate and reduced LOS for obese women with endometrial cancer; with no increase in operative time as BMI rises. Disclosure: Nothing to disclose.